2023
DOI: 10.25300/misq/2022/15713
|View full text |Cite
|
Sign up to set email alerts
|

Where is IT in Information Security? The Interrelationship among IT Investment, Security Awareness, and Data Breaches

Abstract: Data breaches can severely damage a firm’s reputation and its customers’ confidence. Firms must therefore continuously invest in security measures to prevent such breaches. However, the effectiveness of security investment has been questioned by both practitioners and academics. We illustrate the bidirectional dynamic relationship between information technology (IT) investment and data breaches moderated by threat and countermeasure security awareness using an eight-year panel of 311 U.S.-listed firms to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Li et al ( 2021 ) found that IT security investments have different effects on security breaches in organizations with different approaches to making digitalized progress. Li W, Leung ACM, Yue WT ( 2022 ) stated that there is a dynamic interrelationship between IT investments and data breaches. Haislip et al ( 2021 ) found that executives’ IT expertize could be an effective factor influencing reported data security breaches.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al ( 2021 ) found that IT security investments have different effects on security breaches in organizations with different approaches to making digitalized progress. Li W, Leung ACM, Yue WT ( 2022 ) stated that there is a dynamic interrelationship between IT investments and data breaches. Haislip et al ( 2021 ) found that executives’ IT expertize could be an effective factor influencing reported data security breaches.…”
Section: Literature Reviewmentioning
confidence: 99%